'A fine fellow … although rather Semitic': Jews and antisemitism in Jules Verne's Le Château des Carpathes and Bram Stoker's Dracula. Issue 4 (2nd October 2022) - Renshaw, Daniel
ABSTRACT: This article examines the dynamics of fin-de-siècle European antisemitism through the lens of two gothic novels, Jules Verne's Le Château des Carpathes and Bram Stoker's Dracula . The complexities of Verne's depictions of Jews are placed in the wider context of persecution, integration and exclusion, and economic characterisations of 'the Jew' in Western and Eastern Europe. This is compared with the visceral fear of the 'other' as expressed in Dracula . The differences between implicit and explicit prejudice in the two texts are considered as components of the wider antisemitic discourse present in Europe at the end of the nineteenth century.